Selection of Resin-Based Dental Restorative Materials: A Pilot Study on Professional Characteristics, Knowledge, and Selection Criteria - Anna Kontakou Zoniou; Maria Antoniadou; Sofia Saridou (Applied Sciences, 2025)
Resin-based restorative materials are widely used for direct dental restorations due to their versatility and esthetic appeal. However, selecting the most appropriate material involves multifactorial considerations, including clinical demands, practitioner preferences, and professional background. This pilot study aimed to investigate the factors influencing the selection of resin-based restorative materials among dental clinicians at the National and Kapodistrian University of Athens. A structured questionnaire comprising 23 closed-ended and 5 open-ended items was administered to 87 clinicians between October 2023 and January 2025. The survey assessed material preferences for anterior and posterior restorations, along with demographic, economic, and environmental influences. Data were analyzed using descriptive statistics, Spearman correlations, and Mann–Whitney U tests (SPSS v29). Findings revealed that clinicians with over five years of experience demonstrated significantly greater knowledge of material composition (r = 0.230) and shelf life (r = 0.223). These practitioners favored specialized materials, whereas those with less experience emphasized anatomical and esthetic attributes. For posterior restorations, 75.9% of respondents preferred packable composites. Involvement in procurement processes correlated positively with familiarity with ISO specifications (r = 0.254). While environmental concerns were noted, they were generally secondary, with gender-based differences observed in prioritization. These results underline the importance of targeted continuing education to enhance evidence-based material selection in restorative dentistry.